Bacteriophage isolated from Burkholderia pseudomallei causes phenotypic changes in Burkholderia thailandensis - Ladawan Sariya (2018)
Burkhoderia pseudomallei, a causative agent of melioidosis, is a gram-negative bacillus that is closely related to its avirulent counterpart, B. thailandensis. Previous reports suggested that ninety-two percent of B. pseudomallei species carried prophages. In this study, 21 phages isolated from 64 isolates of B. pseudomallei were able to lyse some strains of B. thailandensis and 3 phages converted B. thailandensis to lysogens. By DNase and RNase treatment of the genomes, all these three phages, φC2, φC13 and φC32, were DNA viruses. By nucleic acid type and morphology, φC2 and φC13 were grouped in the Myoviridae family and φC32 was in the Podoviridae family. The φC32 phage described here appears to be the first member of the Podoviridae family that was isolated from Burkholderia spp. To assess the phenotypic changes of B. thailandensis before and after infection with these three phages, the whole-cell protein profile, the resistance to normal human serum (NHS) and the basic biochemical characters were examined and compared. Changes in protein profiles were clearly observed in the T9φC2 and T10φC2 lysogens when compared with the phage-recipients. In addition, while the T10 recipient was sensitive to serum, both lysogenic T10φC2 and its phage-donor C2 grew well in the presence of 30% NHS. There is only one difference in biochemical activities based on the API20NE kit. The phage-recipient T9 could use esculin as an energy source but T9φC2 lysogen and the phage-donor C2 was unable to hydrolyse esculin. The results here suggested that changes in phenotypic characters could occur after B. thailandensis received the phage from B. pseudomallei.